Applied psychology - Davey, Graham (John Wiley & Sons Ltd, 2023)
"For many psychology students, their reason for choosing an undergraduate degree in psychology is their interest in applied psychology and a desire to use psychological knowledge to help solve personal and social problems. With this in mind, this textbook has been designed to satisfy these needs for applied psychology teaching at all undergraduate levels. Applied Psychology, Second Edition will be designed to introduce students to the main areas of applied psychology (clinical, health, educational, occupational, forensic, sport & exercise, counselling, and teaching psychology) from UK, European and international perspectives. It also introduces the cores psychological knowledge that underpins these applied and professional areas. As a result, students learn core knowledge from the five main areas of psychology, as well as acquiring a thorough grounding in how this knowledge is applied, and the professional issues associated with that application"-- Provided by publisher.